Nanoparticles camouflaged in platelet membrane coating as an antibody decoy for the treatment of immune thrombocytopenia. (December 2016) - Wei, Xiaoli; Gao, Jie; Fang, Ronnie H.; Luk, Brian T.; Kroll, Ashley V.; Dehaini, Diana; Zhou, Jiarong; Kim, Hyeon Woo; Gao, Weiwei; Lu, Weiyue; Zhang, Liangfang
Abstract: Immune thrombocytopenia purpura (ITP) is characterized by the production of pathological autoantibodies that cause reduction in platelet counts. The disease can have serious medical consequences, leading to uncontrolled bleeding that can be fatal. Current widely used therapies for the treatment of ITP are non-specific and can, at times, result in complications that are more burdensome than the disease itself. In the present study, the use of platelet membrane-coated nanoparticles (PNPs) as a platform for the specific clearance of anti-platelet antibodies is explored. The nanoparticles, whose outer layer displays the full complement of native platelet surface proteins, act as decoys that strongly bind pathological anti-platelet antibodies in order to minimize disease burden. Here, we study the antibody binding properties of PNPs and assess the ability of the nanoparticles to neutralize antibody activity both in vitro and in vivo . Ultimately, we leverage the neutralization capacity of PNPs to therapeutically treat a murine model of antibody-induced thrombocytopenia and demonstrate considerable efficacy as shown in a bleeding time assay. PNPs represent a promising platform for the specific treatment of antibody-mediated immune thrombocytopenia by acting as an alternative target for anti-platelet antibodies, thus preserving circulating platelets with the potential of leaving broader immune function intact. Graphical abstract: